Adeno-associated virus-mediated expression of activated factor V (FVa) for hemophilia phenotypic correction - Sun, Junjiang; Chen, Xiaojing; Chai, Zheng; Niu, Hongqian; Dobbins, Amanda L.; Nichols, Timothy C.; Li, Chengwen (Frontiers in Medicine, 2022)
AAV gene therapy has been successfully applied in hemophilia patients excluding patients with inhibitors. During the coagulation pathway, activated factor V (FVa) functions downstream as a co-factor of activated factor X (FXa) to amplify thrombin generation; we hypothesize that expression of FVa via gene therapy can improve hemostasis of both Factor IX/ FVIII deficiencies regardless of clotting factor inhibitor. A human FVa (hFVa) expression cassette was constructed and AAV8 vectors encoding hFVa (AAV8/TTR-hFVa) were intravenously administrated into mice with hemophilia A and B with or without FVIII inhibitors. Hemostasis, including hFVa level, activated partial thromboplastin time (aPTT), tail clip, and the saphenous vein bleeding assay (SVBA), were performed. In hemophilia B mice, a dose of 4x1013vg/kg AAV8/TTR-hFVa vectors achieved a complete phenotypic correction over 28 weeks. In hemophilia A mice, hemostasis improvement was also achieved regardless of FVIII inhibitor development. In vivo hemostasis efficacy was confirmed by tail clip and SVBA. Interestingly, while minimal shortening of aPTT was observed at a lower dose of AAV8 vectors, hemostasis improvement was still achieved via in vivo bleeding assays. Collectively, FVa-based AAV gene therapy shows promise for hemostasis correction in hemophilia regardless of inhibitor development and no potential risk for thrombosis.